Traps of psychological diagnosis on example of the Barnum’s effect and so called Adult Children of Dysfunctional Families syndrome - Margasiński, Andrzej (Studia Psychologica: Theoria et praxis, 2013)
The notion of ”adult children of dysfunctional families” has been present for several years in psychological and self-help literature. It arouses controversy due to ambiguity of its definition and unclear diagnosis criteria. The author have attempted to verify empirically so called ACDFs (adult children of dysfunctional families) control list, treated as a diagnostic tool. The second research aim is verification of Barnum effect in Polish circumstances, psychological mechanism which can crucially distort diagnostic conduct. The survey done showed the lack of diagnostic usefulness of most of the ideas connected with so called ACDFs control list, the larger part of which has a non specific, i.e. of Barnum.